Variations of the Intensity of the Siberian High During the Last Glacial Revealed by the Sorting Coefficient of Loess‐Paleosol Deposits in Eastern Central Asia. Issue 9 (20th September 2022) - Cheng, Liangqing; Song, Yougui; Yang, Linhai; Chang, Hong; Wu, Yubin; Long, Hao; Miao, Xiaodong; Dong, Zhibao
Abstract: Eastern Central Asia has an arid environment and experiences frequent dust storms. Modern observations indicate that the dust storm frequency in eastern Central Asia is modulated mainly by the intensity of the Siberian High (SH). However, a lack of knowledge about the process influencing the variation of the SH limits our ability to understand the genesis of dust storms and their predictions. In this study, we present data on heavy mineral assemblages and sediment grain size in a loess section in eastern Central Asia, spanning the last glacial. Combined with previously published results, we propose that the sorting coefficient in loess‐paleosol sequences is a more sensitive proxy for wind intensity—and thus for the intensity of the SH—than the commonly used proxies of the mean grain size and grain size fractions, which are also influenced by changes in dust source and vegetation cover. Our sorting coefficient series clearly reveals Heinrich events, as well as the prominent ∼5 kyr Bond cycle. Larger sorting coefficients correspond to more depleted Sanbao Cave stalagmite δ 18 O values, revealing an antiphase relationship between the intensity of the SH and the East Asian Summer Monsoon during the last glacial. The sorting coefficient series also support the significant influence of Arctic sea‐ice cover on the intensity of the SH. Plain Language Summary: Central Asia is characterized by an arid environment. Dust storms occur frequently in Central Asia. Modern observations indicate that the frequency of dust storms in eastern Central Asia is mainly related to the near‐surface wind intensity, which is modulated by the Siberian High (SH). Therefore, understanding the change process of the SH intensity and its driving mechanism is helpful to effectively predict dust storms in the future. Bulk grain size proxies, such as mean/median grain size or grain size fraction, are usually used to reflect changes in the intensity of the SH, but they will also be affected by other factors such as vegetation coverage and dust provenance. In this study, we first theoretically discuss the potential of sorting coefficient as an indicator of near‐surface wind intensity. The sorting coefficient is then applied to a Central Asian loess section to infer the variation of the SH intensity. In contrast to commonly used mean grain size, sorting coefficients not only clearly reveal Heinrich events but also demonstrate very strong ∼5 kyr cycles, known as the "Bond Cycle". Larger sorting coefficient corresponding to more depleted Sanbao cave stalagmite δ 18 O values indicates an antiphase relationship between the SH and East Asian Summer Monsoon during the last glacial. Key Points: Sorting coefficient is a more sensitive proxy for wind intensity than commonly used proxies of mean grain size and grain size fraction Antiphase relationship between the Siberian High (SH) and East Asian Summer Monsoon during the last glacial Our results support the great influence of the extent of Arctic sea ice on the intensity of the SH